Edukasi Pengendalian dan Pencegahan Infeksi COVID-19 dan Pembagian Masker - Mahyarudin Mahyarudin; Arif Wicaksono; Virhan Novianry (Kapuas, 2021)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a new strain of virus from the coronavirus that can cause mild disorders of the respiratory system, severe lung infections and death. This virus can attack all ages. The disease is called Coronavirus Disease (20) 19 or COVID-19. The transmission of this virus is via droplets spread by coughing or sneezing on an infected person. We cannot know someone has COVID-19 or not, so we have to adopt a clean and healthy lifestyle, and try to protect ourselves using personal protective equipment, one of which is the use of masks. The use of masks can prevent transmission of COVID-19. The purpose of this activity is to educate the public on the importance of using masks. The target of this activity is the people in Pontianak City. The expected output is that the community understands more about the disease and how it is transmitted, so that they will be more disciplined in using masks. Keywords: SARS-CoV-2, Infection Disease Prevention, Mask